Two Pairs of 7,7′-Cyclolignan Enantiomers with Anti-Inflammatory Activities from Perilla frutescens - Jing Zuo; Tian-Hao Zhang; Liang Xiong; Lu Huang; Cheng Peng; Qin-Mei Zhou; Ou Dai (Molecules, 2022)
Perilla frutescens (L.) Britt. (Labiatae), a medicinal plant, has been widely used for the therapy of multiple diseases since about 1800 years ago. It has been demonstrated that the extracts of P. frutescens exert significant anti-inflammatory effects. In this research, two pairs of 7,7′-cyclolignan enantiomers, possessing a cyclobutane moiety, (+)/(−)-perfrancin [(+)/(−)-1] and (+)/(−)-magnosalin [(+)/(−)-2], were separated from P. frutescens leaves. The present study achieved the chiral separation and determined the absolute configuration of (±)-1 and (±)-2. Compounds (+)-1 and (−)-1 have notable anti-inflammatory effects by reducing the secretion of pro-inflammatory factors (NO, TNF-α and IL-6) and the expression of pro-inflammatory mediators (iNOS and COX-2). These findings indicate that cyclolignans are effective substances of P. frutescens with anti-inflammatory activity. The present study partially elucidates the mechanisms underlying the effects of P. frutescens.